THE RELATIONSHIP BETWEEN THE DIABETIC PATIENTS AND THE BUILT ENVIRONMENT: THE ISLAMIC VIEW - Sidawi, Dr.Bhzad; Al-Hariri, Dr. Mohamed Taha Ali (Journal of Islamic Architecture, 2012)
Diabetes mellitus, is a serious disease that may lead to severe conditions such as blindness, end-stage of renaldisease, limb amputation and a variety of debilitating neuropathies. Previous research indicated that diabetesis caused by a complex interaction of patient’s genetics, life-style and environmental factors. It alsohighlighted that providing quality and healthy built environment to citizens including diabetic patients wouldprevent the decline of the patient condition. Accordingly, the Islamic built laws derived from Islamic Shariahave set the grounds of how to provide healthy built environment for citizens. Little research was conducted inthe Kingdom of Saudi Arabia (KSA) in regards to the effect of environmental conditions on the health status ofdiabetic people. In 2011, the present researchers have surveyed a number of diabetic patients to find out thepossible impact of built environment settings on the patient’s lifestyle thus how far it would affect the progressof the diabetes. The results showed a close link between a poor home and environmental settings, the patient’slifestyle, and the health status. The paper argues that certain changes to the built environment must be doneand to provide a healthy and safe environment for diabetic patients. The Islamic built laws would largely helpin provisioning such healthy environment that helps people to live to abandon their bad habits and adopthealthier lifestyle.